Growth Performance and Slaughter Characteristics of Broiler Chickens Fed with Antibiotic, Mannan Oligosaccharide and Dextran Oligosaccharide Supplemented Diets - Bozkurt, M.; Kucukyilmaz, K.; Catli, A.U.; Cinar, M. (International Journal of Poultry Science, 2008)
The aim of the present study was to investigate the effect of dietary supplementation with an antibiotic growth promoter (AGP) and two prebiotics; mannan oligosaccharide (MOS) and dextran oligosaccharide (DOS), respectively, on growth performance and some slaughter characteristics of broilers. One thousand and two hundred day-old broiler chicks (Ross 308) were weighted and randomly assigned to the four treatment groups, each with six replicates. Birds were housed in replicate pens (1.5 x 3.0 m) each containing 50 birds (25 male and 25 female). The four treatments were as follows: 1. Basal diet (Control); 2. Basal diet + antibiotic (10 mg avilamycin/kg diet); 3. Basal diet + mannan oligosaccharide (1 g/kg diet); 4. Basal diet + dextran oligosaccharide (1 g/kg diet). Chicks fed on basal diets were supplemented with an AGP and both of prebiotics were significantly heavier at 21 and 42 days of age than that of control chickens fed with basal diet as control. Besides, body weight of birds given MOS supplemented diet was significantly higher than those birds fed with AGP and DOS added diets (P < 0.05). Feed consumption, feed conversion ratio and liveability of birds was not affected by dietary treatments determined both at 0 to 21 d, 22-42 d and 0-42 d periods (P > 0.05). Percentage weight of carcass yield, liver, pancreas and abdominal fat pad was not affected by dietary treatments also (P > 0.05). The results obtained in the present experiment showed that birds fed with AGP, MOS and DOS supplemented diets exhibited higher body weight gain (P < 0.05) and numerically improved feed efficiency than that of the control birds fed on basal diet. In conclusion, either MOS or DOS could replace for AGP as non-antimicrobial performance enhancer feed additives without scarifying any performance goal and carcass yield of broilers.